Two investment solutions for CTL forestry machines - Eliasson, Oskar (SLU/Dept. of Economics, 2016)
The private owned forestry machinery contractors account for the major part of the harvesting and logging of wood in Sweden. Without contractors the Swedish forestry sector would not be able to harvest any wood in the Swedish forest. A large group of the contractors have struggled with poor liquidity since the nineties. In a sector with low profitability, it is important to make every investment decision in a balanced way and by the right time. If you sell the machine too early you might end up with high financial costs, if you sell to late you might end up with a machine that causes a lot of unwanted downtime and costs. This thesis’ aim is therefore to examine, with the help of a questionnaire and mathematical calculation, if it is more profitable to loan money for a new forestry machine or lease it. To reach the aim this study is carried out through a quantitative manner by both using questionnaire and calculations. In order to obtain data for the calculations the author first conducts a questionnaire to gather information about contractors and their machinery. The results from this survey are then used in order to do correct and truthful calculations. Finding the most economically rational time to replacement for a machine is conducted through a mathematical method based on net present value calculations of annual costs. By using the optimal time for investing in a new machine, a comparison between bank loan and leasing is conducted in order to find which the most economically rational financing solution is. Results from the study show that contractors own their machinery for a time length a bit too short, compared with the most economically lifespan. Only half of the contractors reveal that they do not conduct any calculations of their own, before investing, or take in bids and offers from different vendors before purchasing a new forestry machine. Bank loan appear to be the better option from an economic perspective, but leasing has other advantages that a normal bank loan does not have in form of risk-taking and flexibility.